Diagnóstico de los factores de riesgos psicosociales en las unidades de docencia, investigación y vinculación de la ESPAM MFL - Párraga Palma, María Victoria (2013)
This thesis has served to make an initial determination of psychosocial risk factors in the Polytechnic School of Manabí Agricultural Manuel Felix Lopez and to improve performance in the units of teaching, research and linking of the institution. For the development of this work was used as the survey tool that was addressed to teachers, research areas and social linking (ESPAM MFL), total of 73 responses in the surveyed sample was obtained resulting in a perception of psychosocial risk: psychosocial risk factors were present: double presence, development opportunities at work, influence on work and health is linked to stress, that relate to the performance of employees, their productivity levels and agility to perform tasks perceiving the existence of psychosocial risk low but considering that if nothing is done they can increase, for that reason we develop an improvement program based on the above factors the same were analyzed with the guidelines of the institution making activities or creating solutions with responsibility and date of the execution of the program as possible, considering that the elimination of problems requires continuous monitoring to solve problems that arise.